Lessons and Leadership in Health; Comment on "Improving the World's Health through the Post-2015 Development Agenda: Perspectives from Rwanda" - George Alleyne (Kerman University of Medical Sciences, 2015)
This paper comments on the principles that informed Rwanda's successful efforts to adapt its health system to population needs, and more specifically to reduce health inequities. The point is made that these may be universally applicable for countries as they deal with the challenges of post-2015 health agenda.